STIMULASI PSIKOSOSIAL DAN PENGARUHNYA PADA KARAKTER ANAK YANG BERSEKOLAH DAN TIDAK BERSEKOLAH DI TAMAN BERMAIN SEMAI BENIH BANGSA, KABUPATEN ACEH UTARA, PROVINSI NAD - Dwi Hastuti; Alfiasari Alfiasari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2008)
The research was a part of umbrella research which was conducted to evaluate a preschool model established by Indonesia Heritage Foundation and Exxon Mobil Oil at District Aceh Utara, NAD Province, known as Taman Bermain Anak-Semai Benih Bangsa (TBA-SBB). Study design was a cross sectional survey which was done on April to June 2007. The subdistricts selected in the study was purposively chosen in order to compare performance of those attending TBA-SBB, kindergarten (TK) and non preschooler (no preschool education) as control group of the study. From 7 locations there was 7 TBA-SBB, 7 kindergartens and 7 control group which include 10 children per location, for a total of 210 children and their families as sample of the study. Results showed that psycho-social stimulation of those children attending school (TBA-SBB and TK) was significantly higher than control group, while there was no significance difference found between TBASBB dan TK. Character of children attending TBA-SBB was significantly the highest compare to the two groups, while children from TK was higher than control group. This finding showed that in term of child’s character children from TBA-SBB was better although family social economic status is relatively lower than those children from TK. Statistical analysis found that psycho-social stimulation at home had no significant influence while school background (TBA-SBB>TK) was significantly influenced to child’s character and the influence of TBA-SBB is higher than TK. Beside child’s gender (girls>boys)and increasing age of children also significantly influence to child’s character.